2018
DOI: 10.3389/fphar.2018.01353
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Adherence Based on Prescription or Dispensation Information: Impact on Thresholds and Outcomes. A Real-World Study With Atrial Fibrillation Patients Treated With Oral Anticoagulants in Spain

Abstract: Objective: To estimate drug exposure, Proportion of Days Covered (PDC) and percentage of patients with PDC ≥ 80% from a cohort of atrial fibrillation patients initiating oral anticoagulant (OAC) treatment. We employed three different approaches to estimate PDC, using either data from prescription and dispensing (PD cohort) or two common designs based on dispensing information only, requiring at least one (D1) or at least two (D2) refills for inclusion in the cohorts. Finally, we assessed the impact of adherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 89 publications
1
24
0
2
Order By: Relevance
“…We found 11 observational studies 4 , 5 , 13 , 14 , 30 , 31 , 32 , 33 , 34 , 35 , 36 that investigated adherence of patients to DOAC treatment of which 7 were restricted to atrial fibrillation patients with a follow‐up of more than 6 months. 4 , 5 , 14 , 30 , 31 , 32 , 33 The proportion of atrial fibrillation patients with a PDC of ≥80% in five of these studies ranged from 72% to 77%, 4 , 5 , 14 , 30 , 31 , 32 , 33 which is similar to what we found in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 11 observational studies 4 , 5 , 13 , 14 , 30 , 31 , 32 , 33 , 34 , 35 , 36 that investigated adherence of patients to DOAC treatment of which 7 were restricted to atrial fibrillation patients with a follow‐up of more than 6 months. 4 , 5 , 14 , 30 , 31 , 32 , 33 The proportion of atrial fibrillation patients with a PDC of ≥80% in five of these studies ranged from 72% to 77%, 4 , 5 , 14 , 30 , 31 , 32 , 33 which is similar to what we found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We found 11 observational studies 4 , 5 , 13 , 14 , 30 , 31 , 32 , 33 , 34 , 35 , 36 that investigated adherence of patients to DOAC treatment of which 7 were restricted to atrial fibrillation patients with a follow‐up of more than 6 months. 4 , 5 , 14 , 30 , 31 , 32 , 33 The proportion of atrial fibrillation patients with a PDC of ≥80% in five of these studies ranged from 72% to 77%, 4 , 5 , 14 , 30 , 31 , 32 , 33 which is similar to what we found in our study. The study by Maura et al, which included a total of 22 267 patients with atrial fibrillation, using either dabigatran (n = 11 141) or rivaroxaban (n = 11 126) found a relatively low proportion of patients using a DOAC with a PDC of ≥80% (61%).…”
Section: Discussionmentioning
confidence: 99%
“…Good adherence, defined as PDC >0.80, is associated with reduced risk of all-cause mortality (hazard ratio [HR], 0.86; 95% confidence interval [CI], 0.81–0.91) and ischaemic stroke (HR, 0.69; CI, 0.56–0.85) as shown from data from the Valencia Health System database in Spain (n=37,774) 50). Conversely, poor adherence (PDC<0.80) at 12-month follow-up is associated with a significantly higher risk of both ischaemic stroke (HR, 2.08; CI, 1.11–3.88) and deep vein thrombosis (HR, 5.39; CI, 1.78–16.3) 51).…”
Section: Patient Persistence and Adherence With Oral Anticoagulant Thmentioning
confidence: 99%
“… 3 The better adherence or persistence to DOAC compared to VKA is still being discussed, as studies have yet to find any differences, 4 including in France. 5 Furthermore, several studies have shown that non-adherence to VKA therapy was associated with an increased risk of stroke, 6 similarly to DOAC. 3 , 7 Nevertheless, very few studies have reported the association between non-adherence to DOAC and the incidence of thrombo-embolic events, and almost none after more than 1-year of follow-up.…”
Section: Introductionmentioning
confidence: 99%